RESULTS OF IMPLEMENTING DIGITAL MODULES OF THE ITTS PLATFORM WITHIN THE DISCIPLINE «INFORMATION TECHNOLOGIES IN TECHNICAL SYSTEMS - Elena Kodirova (Bright Mind Publishing, 2026)
The article presents the results of implementing digital modules of the Information Technologies in Technical Systems (ITTS) platform into the educational process within the discipline “Information Technologies in Technical Systems” during the fourth quarter of 2025. A comprehensive analysis was conducted, including quantitative and qualitative indicators covering educational, methodological, and technical aspects. It was established that the use of digital modules contributed to the improvement of academic performance, increased student engagement, and the development of independent learning skills. The methodological component ensured the structuring and multimedia enrichment of learning materials, as well as their compliance with national and international standards of engineering education. Technical indicators confirmed the stability and adaptability of the platform, which enabled its successful integration into the university’s LMS. The obtained results are consistent with national and international studies in the field of educational digitalization and confirm the effectiveness of the chosen strategy. The practical significance of the study lies in the possibility of applying the proposed analytical methodology and identified results to improve curricula, develop new digital modules, and prepare faculty members for teaching in a digital learning environment.
Keywords: Educational digitalization; engineering education; digital modules; LMS; educational platforms; academic performance; methodological support.